A Review Paper on Solar Power Monitoring System using an IoT - Patil, Vishal S; Morey, Aparna P; Chauhan, Gauri J; Bhute, Suraj S; Borkar, Tejaswini S (International Journal of Computer Sciences and Engineering, 2019)
The solar power monitoring system is used the Internet of Things for the purpose, to overcome the drawbacks of previous solar systems. An IoT is a joint network of the connected devices together and shares the data about how they are used in the environment in which they are operated. The solar power monitoring system is used for generating the electricity by using the energy of sunlight. This system is uses the Arduino Uno for enhancement of the solar systems. This solar power monitoring system uses the Arduino Uno. The Arduino Uno is microcontroller board, this microcontroller used the ATmega328p. ATmega328p is also a microcontroller chip which is developed by Atmel. By using Arduino Uno the solar panel is capable of moving in the direction where sunlight is moves , this is the additional feature of this solar system. This paper shows the working, architecture and connections of the solar power monitoring system using an IoT.